2021
DOI: 10.3390/antiox10101583
|View full text |Cite
|
Sign up to set email alerts
|

ER-Mitochondria Calcium Flux by β-Sitosterol Promotes Cell Death in Ovarian Cancer

Abstract: Phytosterols, which are derived from plants, have various beneficial physiological effects, including anti-hypercholesterolemic, anti-inflammatory, and antifungal activities. The anticancer activities of natural products have attracted great attention, being associated with a low risk of side effects and not inducing antineoplastic resistance. β-sitosterol, a phytosterol, has been reported to have anticancer effects against fibrosarcoma and colon, breast, lung, and prostate cancer. However, there are no report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 47 publications
1
32
1
Order By: Relevance
“…Vitro experiments have shown that several phytosterols, including campesterol, β-sitosterol, and stigmasterol, exerted anticancer effect on OC, which provided potential biological mechanisms for our findings. These phytosterols activated proapoptotic signals and induced the apoptosis of OC cells, simultaneously upregulated the calcium levels of cytosolic and mitochondrial and caused excessive calcium overload (34)(35)(36), which further promoted the cell apoptosis (37,38). Besides, these phytosterols promoted the overexpression of unfolded protein response and endoplasmic reticulum-mitochondria axis signals, which triggered cell apoptosis pathway and autophagic stimulus and caused endoplasmic reticulum stress (34)(35)(36)39), the accumulation of endoplasmic reticulum stress induced the cancer cells death (40).…”
Section: Discussionmentioning
confidence: 99%
“…Vitro experiments have shown that several phytosterols, including campesterol, β-sitosterol, and stigmasterol, exerted anticancer effect on OC, which provided potential biological mechanisms for our findings. These phytosterols activated proapoptotic signals and induced the apoptosis of OC cells, simultaneously upregulated the calcium levels of cytosolic and mitochondrial and caused excessive calcium overload (34)(35)(36), which further promoted the cell apoptosis (37,38). Besides, these phytosterols promoted the overexpression of unfolded protein response and endoplasmic reticulum-mitochondria axis signals, which triggered cell apoptosis pathway and autophagic stimulus and caused endoplasmic reticulum stress (34)(35)(36)39), the accumulation of endoplasmic reticulum stress induced the cancer cells death (40).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SIT stimulated apoptosis in breast cancer MDA-MB-231 cells by increasing the Bax/Bcl-2 ratio and promoting mitochondrial membrane depolarization ( 27 ). Further, SIT elevated the expression level of Bax, Bcl-2 antagonist/killer (Bak), caspase-3 and -9, and cytochrome C in ovarian cancer cells (ES2 and OV90) in a dose-dependent manner ( 28 ). This data indicates that SIT upregulates pro-apoptotic signals in ovarian cancer cells.…”
Section: Induction Of Tumor Cell Apoptosis After Sit Interventionmentioning
confidence: 99%
“…In another study, Bae et al. pretreated cells with N-acetylcysteine (NAC) for 1 h before SIT treatment to assess the relationship between SIT-induced mitochondrial dysfunction and ROS production ( 28 ). The results showed that NAC could partially inhibit SIT-induced loss of mitochondrial membrane potential (MMP) in ovarian cancer cells (OV90), suggesting that SIT mainly exerted adverse effects on mitochondria and indirectly disrupted ROS homeostasis.…”
Section: Induction Of Tumor Cell Apoptosis After Sit Interventionmentioning
confidence: 99%
See 2 more Smart Citations